2012
DOI: 10.1111/j.1365-2265.2011.04268.x
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary microsurgical concept for the treatment of Cushing’s disease: endocrine outcome in 83 consecutive patients

Abstract: With our microsurgical concept, a high initial cure rate is achievable with minimal surgical morbidity. Enlarged adenomectomy has no adverse effect on the rate of postoperative hypopituitarism. Early repeat surgery is a successful option if CD persists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 39 publications
3
36
1
1
Order By: Relevance
“…This compares favorably with previously reported remission rates after microscopic TS in patients with ACTH-secreting macroadenomas which are on average 60%, despite the fact that most studies used less strict criteria for remission than we used (Table 2) (5,7,8,9,10,13,14,15,16,34,35,36). In line with our results, Starke et al recently reported a high remission rate of 87% in patients with ACTH-secreting macroadenomas (nZ15, of which six were invasive), achieved with endoscopic TS.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This compares favorably with previously reported remission rates after microscopic TS in patients with ACTH-secreting macroadenomas which are on average 60%, despite the fact that most studies used less strict criteria for remission than we used (Table 2) (5,7,8,9,10,13,14,15,16,34,35,36). In line with our results, Starke et al recently reported a high remission rate of 87% in patients with ACTH-secreting macroadenomas (nZ15, of which six were invasive), achieved with endoscopic TS.…”
Section: Discussionsupporting
confidence: 81%
“…These reports show that, in experienced hands, excellent remission rates of over 80% can be achieved if a microadenoma is visualized on preoperative imaging (5,6,7,8,9,10,11,12,13,14,15,16). However, if no adenoma is visualized on preoperative imaging (magnetic resonance imaging (MRI)-negative CD), or if a macroadenoma is the cause of CD, remission rates are substantially lower (5,6,7,8,9,10,13,14,15,16). Furthermore, CD relapses in up to 25% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were again in accordance with published series, as patients with macroadenomas experienced after first TSS lower remission rates compared with those with microadenomas (69 vs 79%). Of course, we have to concede that our cohort harbored a high prevalence of macroadenomas (27%) when compared with other series (20,21,25); this might be due to the fact that our endocrinology departments serve as referral centers for difficult, complicated cases.…”
Section: First Tssmentioning
confidence: 99%
“…Lack of consensus regarding remission criteria of CD has led to a broad range of recurrence rates reported (25). A comprehensive review of large clinical studies reveals a recurrence rate of 20-25% 10 years after surgery (4).…”
Section: First Tssmentioning
confidence: 99%
“…Since 2010, surgical series generally show remission rates between 65% and 85% and recurrence rates of 10%-35% (Table 1). [1][2][3]5,8,20,24,25,27,41,44,53,86,97,99,101,107 Surgical success and recurrence rates depend on surgeon experience, as well as the criteria used to define cure and length of follow-up.…”
mentioning
confidence: 99%